Inflammation mediates the effect of adiposity and lipid metabolism indicators on the embryogenesis of PCOS women undergoing in vitro fertilization/intracytoplasmic sperm injection - Jiang, Huahua; Chen, Lixue; Tian, Tian; Shi, Huifeng; Huang, Ning; Chi, Hongbin; Yang, Rui; Long, Xiaoyu; Qiao, Jie (Frontiers in Endocrinology, 2023)
Background: Polycystic ovary syndrome (PCOS) is a complex reproductive endocrine and metabolic disease affecting women of reproductive age. The low-grade chronic inflammation in PCOS is considered to be associated with obesity and dyslipidemia. We aim to investigate the potential mediating role of WBC count, a representative inflammatory marker, in the effect of adiposity and lipid metabolism indicators on IVF/ICSI outcomes in PCOS women.We conducted a retrospective cohort study of 1534 PCOS women who underwent their first IVF/ICSI cycles with autologous oocytes at a reproductive center from January 2018 to December 2020. The associations between PCOS women's adiposity and lipid metabolism indicators and WBC count and IVF/ICSI outcomes were examined using multivariable generalized linear models. Mediation analyses were conducted to evaluate the possible mediating role of WBC count.We found significant dose-dependent correlations between adiposity and lipid metabolism indicators and IVF/ICSI outcomes (i.e., hormone levels on the ovulatory triggering day, oocyte development outcomes, fertilization, early embryo development outcomes, and pregnancy outcomes) (all P < 0.05), as well as between adiposity and lipid metabolism indicators and WBC count (all P < 0.001). Increasing WBC count was associated with adverse oocyte and embryonic development outcomes (all P < 0.05). Mediation analyses suggested that increasing serum TG and LDL-C levels and decreasing serum HDL-C level were significantly associated with reduced high-quality Day 3 embryo count in PCOS women, with 21.51%, 9.75%, and 14.10% proportion mediated by WBC count, respectively (all P < 0.05).We observed significant associations between lipid metabolism indicators and high-quality Day 3 embryo count in PCOS women, partially mediated by inflammation-related mechanisms, suggesting the potential intervention target for improving embryo quality in PCOS women.